Hubungan Etika Komunikasi dengan Perilaku Remaja Generasi Z - Muhammad Dhia Luthfi Ramadhan; Tresna Wiwitan (Bandung Conference Series: Public Relations, 2024)
Abstract. Ethics comes from the Greek "ethos" meaning a place of residence, a meadow, a cage, customs, morals, character, feelings, and ways of thinking. But the word "tha etha" means custom. Ethics comes from ethics which means the habit of norms, values, norms and measures of good and bad human behavior. According to data collected by the Ministry of Information and Information Technology of the Republic of Indonesia, 99.79 million Indonesians have used social media touch as their means of communication. This study aims (1) to find out the relationship between the ethics of communication and the behaviour of the Z-generation teenager on the social media, to know the connection between keeping speech with the behavior of generation Z teenagers on the ticker, (2) to learn the relationship of politeness and decency with the conduct of the generation Z-adolescent on theticker, (3) to learn about the relation between the effective and efficient use of language and the conductedness of the generation Z teenager in the ticquer, (4) to know about the connection of mutual appreciation and behaviours of the youth of the Generation Z on a ticker. Social learning theory is used as a platform in punishment. Quantitative research using correlational approaches. The population in this study is the z generation of the youth in the city of Bandung who use social media ticking a total of 397,000 people and the sample in this research uses the Slovin calculation formula using the error rate of 10% then obtained a sample of as much as 97 people. The correlation test results showed a positive result of 0.577 of the 1,000 coefficient intervals, so it can be found that the ethical relationship of communication has a positive influence on the behavior of the z-generation youth in social media. Human behaviour in the context of the continuing interaction of cognitive, behavioral and environmental influences. Abstrak. Etika berasal dari bahasa Yunani “ethos” memiliki arti tempat tinggal, padang rumput, kandang, adat istiadat, akhlak, watak, perasaan, dan cara berpikir. Adapaun dalam bentuk jamak “tha etha” artinya adat kebiasaan. Etika berasal darikata ethikus yang berarti kebiasaan norma-norma, nilai-nilai, kaidah-kaidah, dan ukuran-ukuran baik dan buruk tingkah laku manusia. Media sosial yang menjadi populer di Indonesia dengan jumlah penggguna lebih dari 167 juta orang di semua platform media sosial. Berdasarkan data yang telah diambil oleh kementrian informasi dan informatika Republik Indonesia 99,79 juta penduduk Indonesia telah menggunakan media sosial tiktok sebagai alat komunikasi mereka. Penelitian ini bertujuan (1) untuk mengetahui hubungan antara etika komunikasi dengan perilaku remaja generasi Z di media sosial tiktok, Untuk mengetahui hubungan antara menjaga ucapan dengan perilaku remaja generasi Z di tiktok (2) Untuk mengetahui hubungan antara sopan dan santun dengan perilaku remaja generasi Z di tiktok (3) Untuk mengetahui hubungan antara penggunaan bahasa yang efektif dan efisien dengan perilaku remaja generasi Z di tiktok (4) Untuk mengetahui hubungan antara rasa saling menghargai dengan perilaku remaja generasi Z di tiktokm(5)Untuk mengetahui hubungan emosional dengan perilaku remaja generasi Z di tiktok. Teori belajar sosial digunakan sebagai landassan dalam penelltian. Penelitian kuantitatif dengan menggunakan pendekatan korelasional. Populasi pada penelitian ini yaitu mahasiswa remaja generasi z di Kota Bandung yang menggunakan media sosial tiktok berjumlah 397.000 orang dan sampel pada penelitian ini menggunakan rumus penghitungan slovin dengan menggunakan tingkat error 10% maka diperoleh sampel sebayak 97 orang. Dengan teknik pengambilan sampel yaitu simple random sampling. Hasil uji korelasi menunjukan hasil positif 0.577 dari interval koefisien 1,000 maka dapat diketahui bahwa hubungan etika komunikasi memiliki pengaruh positif dengan perilaku remaja generasi z di media sosial tiktok .Perilaku manusia dalam konteks interaksi timbal balik yang berkesinambungan antara kognitif, perilaku dan pengaruh lingkungan.